Respons Indonesia Dalam Persaingan Militer Di Asia Tenggara - Yoan Pellokila (Jurusan Ilmu Hubungan Internasional, 2016)
A few decades, Southeast Asia region saw a massive military build-up. To some extent it is motivated by growing external and internal threats facing by countries in the region, as well as steady economic growth. Amongst countries such as Malaysia, Singapore, Vietnam, and Thailand have been undergoing military modernisation through military procurement. This paper seeks to find out how does Indonesia respond to the military modernisation if not military competition in the region. This paper argues that Indonesia has been conducting military modernisation through so-called Minimum Essential Forces Policy. Among other Indonesia’s important responses are military cooperation and procurement from many countries, conducting joint military operation, and strengthening national military industry.